An Analysis of Women's Representation in Parliament: A Comparative Study of Indonesia and Other Countries Around the World - Makmun, Makmun; Yandi, Yandi (Dinasti Research, 2025)
This study aims to analyze the factors influencing women's representation in parliament and to compare descriptive and substantive representation of women in Indonesia, Finland, and Timor-Leste. The key factors examined include the electoral system, nomination patterns, parliamentary thresholds, and the internal dynamics of political parties. This research employs a comparative study with a qualitative approach through document analysis and observation of women's political practices in the three countries. The findings reveal that countries with proportional electoral systems and the implementation of party quotas, such as Finland, have a higher proportion of women in parliament. Finland excels in descriptive representation due to strong gender equality and high levels of women's political participation. Timor-Leste has also succeeded in enhancing women’s representation through the effective implementation of gender quotas, while Indonesia faces challenges under its open-list system, which is less supportive of female candidates. In terms of substantive representation, women parliamentarians in Finland and Timor-Leste actively engage with civil society through umbrella organizations and women's caucuses. In contrast, the role of the women’s caucus in Indonesia’s House of Representatives (DPR RI) remains limited. This study recommends enhancing women's political participation through the implementation of legislative quotas, improvements in candidate list ranking quotas, and strengthening communication between women parliamentarians and civil society, as well as empowering the role of the women’s caucus in the DPR RI. Comprehensive political education for women is also considered a crucial step in optimizing women's representation in Indonesia's parliament.